Upregulation of the proto-oncogene Bmi-1 predicts a poor prognosis in pediatric acute lymphoblastic leukemia - Peng, Hong-Xia; Liu, Xiao-Dan; Luo, Zi-Yan; Zhang, Xiao-Hong; Luo, Xue-Qun; Chen, Xiao; Jiang, Hua; Xu, Ling (BMC cancer, 2017)
Bmi-1, the B cell-specific moloney murine leukemia virus insertion site 1, is a member of the Polycomb-group (PcG) family and acts as an oncogene in various tumors; however, its expression related to the prognosis of pediatric patients with acute lymphoblastic leukemia (ALL) has not been well studied. The Bmi-1 expression levels in the bone marrow of 104 pediatric ALL patients and 18 normal control subjects were determined by using qRT-PCR. The association between the Bmi-1 expression and the clinicopathological characteristics of pediatric ALL patients was analyzed, and the correlation between Bmi-1 and the prognosis of pediatric ALL was calculated according to the Kaplan-Meier method. Furthermore, the association between Bmi-1 expression and its transcriptional regulator Sall4 was investigated. Compared to normal control subjects, patients with primary pediatric ALL exhibited upregulated levels of Bmi-1. However, these levels were sharply decreased in patients who achieved complete remission. A significant positive association between elevated Bmi-1 levels and a poor response to prednisone as well as an increased clinical risk was observed. Patients who overexpressed Bmi-1 at the time of diagnosis had a lower relapse-free survival (RFS) rate (75.8%), whereas patients with lower Bmi-1 expression had an RFS of 94.1%. Furthermore, in ALL patients, the mRNA expression of Bmi-1 was positively correlated to the mRNA expression of Sall4a. Taken together, these data suggest that Bmi-1 could serve as a novel prognostic biomarker in pediatric primary ALL and may be partially regulated by Sall4a. Our study also showed that Bmi-1 could serve as a new therapeutic target for the treatment of pediatric ALL.